2010
DOI: 10.1111/j.1475-5661.2010.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

The biopolitics of food provisioning

Abstract: Beginning with Foucault's writing on food provisioning in the mercantile period, this paper explores how a moral economy of hunger is gradually replaced by a political economy of food security that promotes market mechanisms as a better protection against scarcity. In Western Europe the emergence of political liberalism and laissez-faire economics substantially shaped how hunger and scarcity were conceptualised and socially managed. Beyond Europe these social forces were manifest in the development of colonial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
94
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 69 publications
0
94
0
2
Order By: Relevance
“…We follow Foucault in understanding neoliberal ideology to be accompanied by and made manifest through distinct governmentalities (techniques and technologies for managing people and nature) and embodied practices in social, material, and epistemological realms. Combined, these work as biopower to construct and regulate life and lives in significant ways (Nally 2011). We commence with the assertion that there has been a conflation of what is generally (and simplistically) referred to in conservation discourses as economics with the ideological assumptions of neoliberalism.…”
Section: Introductionmentioning
confidence: 99%
“…We follow Foucault in understanding neoliberal ideology to be accompanied by and made manifest through distinct governmentalities (techniques and technologies for managing people and nature) and embodied practices in social, material, and epistemological realms. Combined, these work as biopower to construct and regulate life and lives in significant ways (Nally 2011). We commence with the assertion that there has been a conflation of what is generally (and simplistically) referred to in conservation discourses as economics with the ideological assumptions of neoliberalism.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier definitional work by Maxwell (1996, p. 155) suggested that thinking about food security had shifted from the global and the national to the household and the individual; yet, much of the current emphasis on food security counters this shift and is global in perspective, as noted in commentaries which explain the origins and dynamics of the global food crisis (Jarosz, 2009;Lawrence et al, 2010;McDonald, 2010;McMichael, 2009). In a reading of World Bank and the United Nations Food and Agriculture Organization policy texts on food security, Jarosz (2011 see also Nally, 2011) argues that scaled definitions of food security have been used to serve neoliberal ideology, which more recently includes linking individuals to global modalities of governance that emphasise the instrumentality of agricultural productivity in development strategies.…”
Section: Introductionmentioning
confidence: 99%
“…But racialization within cities is more than just containment. Newman (2005) argues that social groups (both dominant and subordinate) are the objects of governance through the institution of boundaries and borders; of categories, rules, and procedures that define and organise populations as racialized, most often to align with creating economic advantage for one group over all others (see also Nally 2011). Consequently racialized (and classed) constructions extend through the city via its systems.…”
mentioning
confidence: 99%
“…Distinct populations are made through the ways in which they are made visible in space, given access to space and given the authority to control that space via institutions that serve the interests of capital (Nally 2011). Mori argues (2008Mori argues ( :1467 biopower is also "deeply involved in capitalism, particularly because biopolitics regards the human body as a population, regulating it for capital accumulation and redistributing it into proper spaces."…”
mentioning
confidence: 99%